A Comprehensive Analysis of the Role of Parents in 21st-Century Character Education: A Systematic Literature Review - Sugiarti Sugiarti; Islawati Islawati (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to comprehensively analyze the role of parents in children’s character education in the 21st century using a Systematic Literature Review (SLR) approach. The method involved identification, screening, and selection processes following the PRISMA framework, with data sourced from the Scopus database within the 2022–2026 publication range. A total of 9 articles met the inclusion criteria and were analyzed. The findings indicate that parental roles are multidimensional, encompassing family environment, family structure, socioeconomic conditions, values and attitudes, parenting styles, social influence, and role modeling. Furthermore, parental influence on children’s character operates through both direct and indirect mechanisms, including family environment mediation, emotional regulation, value internalization, peer influence, and modeling processes. The study also identifies research gaps, particularly the lack of integrative approaches and limited focus on the 21st-century context. In conclusion, parents play a significant role in shaping children’s character, highlighting the need for a holistic, family-based character education approach.